Love and math : the heart of hidden reality - Frenkel, Edward, 1968- (New York : Basic Books, a member of the Perseus Books Group, 2013)
"Love and Math tells the two intertwined stories of mathematics and the adventure of one man in learning it. The result is a story about how he became one of the twenty-first century's leading mathematicians, working on one of the biggest ideas to come out of mathematics in the last 50 years: the Langlands Program. As Frenkel proves, a mathematical formula can be as elegant and beautiful as a painting, a poem, or a piece of music. And the process of creating new mathematics is just that, an artistic pursuit--a deeply personal experience, which requires passion, dedication, and love. In Love and Math, Frenkel shows readers the aesthetic--and the truly powerful--side of mathematics, and enables appreciation of the field even from those who have long been terrified by it."--
A mysterious beast -- The essence of symmetry -- The fifth problem -- Kerosinka -- Threads of the solution -- Apprentice mathematician -- The Grand Unified Theory -- Magic numbers -- Rosetta Stone -- Being in the loop -- Conquering the summit -- Tree of knowledge -- Harvard calling -- Tying the sheaves of wisdom -- A delicate dance -- Quantum duality -- Uncovering hidden connections -- Searching for the formula of love.
Includes bibliographical references (pages 247-282) and index.
Keywords: Frenkel, Edward, -- 1968-; Mathematicians -- United States -- Biography; Mathematics -- Miscellanea